2018
DOI: 10.1007/s13337-018-0441-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dried blood spot as an alternative sample collection method for hepatitis C virus RNA quantitation and genotyping using a commercial system

Abstract: Dried blood spot (DBS) is a minimally invasive sampling method suitable for sample collection, storage and transportation in resource limited areas. Aim of this study was to compare the diagnostic utility of DBS with plasma sample for HCV RNA quantitation and genotyping using commercial systems. Plasma and DBS card spotted samples were collected from 95 HCV seropositive patients. Both types of samples were subjected to HCV RNA by real-time PCR (Abbott m2000rt, USA). Genotyping was performed using Abbott HCV ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 25 publications
5
16
0
Order By: Relevance
“…This begins to suggest that dried blood spots can be used as an alternative to plasma samples and that the process of adding and removing the sample from the card is not altering the composition of the lipidome and its association with relationship with outcome measures, in this case the concentration of the four 'clinical lipids'. This finding is keeping with previous reports that have shown DBS as a viable alternative (Koulman et al 2014;Mahajan et al 2018) however this is the first study to directly this comparability.…”
Section: Discussionsupporting
confidence: 92%
“…This begins to suggest that dried blood spots can be used as an alternative to plasma samples and that the process of adding and removing the sample from the card is not altering the composition of the lipidome and its association with relationship with outcome measures, in this case the concentration of the four 'clinical lipids'. This finding is keeping with previous reports that have shown DBS as a viable alternative (Koulman et al 2014;Mahajan et al 2018) however this is the first study to directly this comparability.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 8 (2.5%) patients had plasma HCV viral load <1000 IU/mL, and amongst these latter five patients had plasma HCV viral load between 53 and 118 IU/mL that was not detected with DBS. Interestingly, very low HCV viral loads, comparable to those observed in this study, were also reported in a study in India and in a small series of genotype 1 HCV patients in Alaska . Of these five patients in our study, two were newly diagnosed (within a week from enrolment) and one was diagnosed 3 months prior to enrolment; although unable to confirm this, these patients could be in the acute phase of the infection.…”
Section: Discussionsupporting
confidence: 87%
“…Only five patients were not detected as viremic in DBS, but these patients presented with very low plasma HCV viral load ranging from 53 to 118 IU/mL. Similar results have also been observed in other studies that also used the Abbott m 2000 sp/rt system in high‐end laboratories in developed countries or in developing countries . Interestingly, one patient had a low plasma HCV viral load of 83 IU/mL that was also detected in both venous and capillary DBS.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations